2018
DOI: 10.1111/jebm.12303
|View full text |Cite
|
Sign up to set email alerts
|

“A waste of time without patients”: The views of patient representatives attending a workshop in evidence‐based practice

Abstract: BackgroundShared decision‐making is a central element of evidence‐based practice (EBP). Training in EBP has traditionally focused on providers, but there is an increasing interest in developing such educational resources for patients. The aim of this study is to explore the views of patient representatives attending a workshop in EBP.MethodsWe conducted three focus groups with participants attending EBP workshops in 2013, 2014, and 2015. We used the framework method for content analysis. We reviewed the transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
(104 reference statements)
0
1
0
3
Order By: Relevance
“…In another sense, stakeholders who are not professionally employed in health fields increasingly serve as authors of publications, attendees of professional conferences, and reviewers of papers and grant proposals. A study of patient participants in workshops on evidence-based practice reported the view that these workshops are "a waste of time without patients" (Austvoll-Dahlgren & Johansen, 2018). Stakeholders can also review proposals for funding, study protocols for ethical conduct of research, and safety incidents for improvement opportunities.…”
Section: Types Of Stakeholder Participation: Advisors Co-designers mentioning
confidence: 99%
“…In another sense, stakeholders who are not professionally employed in health fields increasingly serve as authors of publications, attendees of professional conferences, and reviewers of papers and grant proposals. A study of patient participants in workshops on evidence-based practice reported the view that these workshops are "a waste of time without patients" (Austvoll-Dahlgren & Johansen, 2018). Stakeholders can also review proposals for funding, study protocols for ethical conduct of research, and safety incidents for improvement opportunities.…”
Section: Types Of Stakeholder Participation: Advisors Co-designers mentioning
confidence: 99%
“…1, [9][10][11][12][13][14][15][16] Günümüzde sağlık bakım hizmetlerinin maliyetinin artması ve KDU'ın bakımın maliyetini azalttığının fark edilmesi, hasta ve ailesinin bilgi talebindeki artış, sağlık bakımında yaşanan tutarsızlıklar, hastaların tedavi ile ilgili endişeleri ve sağlık profesyonelinin bilgi yetersizliği kanıta dayalı uygulamaların gerekliliğini ortaya çıkarmaktadır. 2,10,13,17 KDU'ın ebelik mesleğinde kullanılması, kaliteli ve nitelikli bakım sunulmasına ve ebelik mesleğinin profesyonelleşmesine yardımcı olacaktır. 11,17 Bu konuda geleceğin sağlık profesyonelleri olan ebelik öğrencilerinin mezun olmadan önce KDU konusunda yeterli ve doğru bilgiye sahip olması oldukça önemlidir.…”
Section: Introductionunclassified
“…2,10,13,17 KDU'ın ebelik mesleğinde kullanılması, kaliteli ve nitelikli bakım sunulmasına ve ebelik mesleğinin profesyonelleşmesine yardımcı olacaktır. 11,17 Bu konuda geleceğin sağlık profesyonelleri olan ebelik öğrencilerinin mezun olmadan önce KDU konusunda yeterli ve doğru bilgiye sahip olması oldukça önemlidir. [7][8][9][10][11][12][13][14][15][16][17][18] Pek çok ülkede hastaların ve öğrencilerin KDU ile ilgili farkındalıklarını değerlendiren çalışmalar yapılmıştır.…”
Section: Introductionunclassified
See 1 more Smart Citation